Comparison between Robot-Assisted Laparoscopic Hysterectomy and Total Laparoscopic Hysterectomy: A Cohort Study. (7th August 2012) - Sakhel, Khaled; Kirakosyan, Armen; Chauhan, Suneet; Lukban, James; Hines, James
Abstract : Objective . To compare the operative outcomes in patients who underwent robot-assisted total laparoscopic hysterectomy (RLH) versus total laparoscopic hysterectomy (TLH). Study Design . Retrospective chart review. All women who underwent RLH in hospital A and TLH in hospital B by a single surgeon were included. Results . 136 patients were included (73 in the RLH group and 63 in the TLH group). There were no conversions to laparotomy in the RLH group versus 7 (11.1%) in the TLH group (P = 0.004 ). The mean induction time was significantly greater (by 6 minutes) for RLH, independent of docking time, as compared to TLH (P < 0.001 ). Total procedure time was significantly less in the RLH group (82 minutes) as compared to TLH (108 minutes) (P = 0.001 ). Mean blood loss was less for RLH (46 mL) as compared to TLH (114 mL) (P < 0.001 ). A greater number of patients who underwent RLH were discharged on postoperative day 0 as compared to those receiving TLH (P = 0.055 ). Conclusion . RLH is a safe alternative to TLH and may offer some operative advantages, including fewer conversions to laparotomy, reduced procedure time, less blood loss, and earlier discharge.